Association of insulin and insulin propeptides with an atherogenic lipoprotein phenotype. - Båvenholm, P; Karpe, F; Proudler, A; Tornvall, P; Crook, D; Hamsten, A (1995)
A characteristic lipoprotein phenotype, including hypertriglyceridemia, a low high-density lipoprotein (HDL) cholesterol concentration, and a predominance of small, dense low-density lipoprotein (LDL) particles, is linked to insulin resistance and hyperinsulinemia. Individuals with these characteristics are supposed to be at increased risk of developing coronary heart disease (CHD). To address this issue further, relations between basal and postload glucose, insulin and insulin propeptide concentrations and subfractions of apolipoprotein (apo) B-containing lipoproteins were examined in 62 consecutive Swedish nondiabetic men who had experienced a first myocardial infarction before the age of 45. A total of 41 age-matched, population-based healthy men were investigated as controls. Highly specific immunoradiometric assays were used for measuring intact proinsulin and des 31,32proinsulin levels. In all, 39% of the patients were found to be glucose-intolerant, and basal and postload hyper(pro)insulinemia were characteristic features irrespective of glucose tolerance category. Hypertriglyceridemic (HTG) lipoprotein phenotypes with a low HDL cholesterol concentration dominated among the patients, and hyperinsulinemia was linked to hypertriglyceridemia and putatively atherogenic lipoprotein traits, such as increased particle numbers of small very-low-density lipoprotein (VLDL) and intermediate-density lipoprotein (IDL) and triglyceride enrichment of LDL. The corollary of these findings is that insulin resistance is a characteristic feature of young postinfarction patients and is accompanied by a complex atherogenic lipoprotein phenotype, new components of which are an abundance of small cholesteryl ester-rich VLDL and an elevated LDL triglyceride concentration.